Pengaruh Kepuasan Kerja dan Komitmen Organisasional Terhadap Kualitas Layanan Di PT. Asuransi Jasindo (Persero) Kantor Cabang Korporasi Dan Ritel Bandung. - Haris, Henry; , Drs. Farid Wajdi, MM., Ph.D; , Dr. Anton Agus Setyawan, SE, M.Si (2017)
This study aims to determine job satisfaction, organizational commitment and service quality as well as to analyze the influence of job satisfaction and organizational commitment to the service quality. The object of this research is PT. Asuransi Jasindo (Persero) Corporate and Retail Branch Office Bandung. Descriptive method is used with quantitative approach. Data collection techniques used were observation, interviews and questionnaires with a sample of 70 people. The hypothesis tested by using path analysis. The results showed that job satisfaction, organizational commitment, and quality of service are in the quite well category. Job satisfaction has reached 18.93% influence on service quality, organizational commitment has the effect of 29.79% of job satisfaction. Overall influence of service quality and organizational commitment on service quality is 48.72%.